2014
DOI: 10.4314/jab.v80i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Test d’efficacité d’un herbicide en culture d’ananas, à la station d’expérimentation et de production d’Anguédédou en Côte d’Ivoire

Abstract: Test d'efficacité d'un herbicide en culture d'ananas et de production d'Anguédédou en Côte d'Ivoire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The residue of G-based herbicides and its main metabolites, Aminomethylphosphonic acid (AMPA), are also found in foods, feed and ecosystems (Takahashi et al, 2001;Acquavella et al, 2004;Contardo-Jara et al, 2008). The consequences of the potential effects of these compounds on non-target organisms, such as humans or animals, have been highlighted (Williams et al, 2000;Tomlin 2006;Mangara et al, 2014). Besides, several studies have pointed out that these chemicals can adversely affect endocrine, reproductive, immune and renal systems (Gasnier et al, 2009;Clair et al, 2012;Mink et al, 2012).Recently, we showed that KL is an endocrine disruptor, which can interfere with the female reproductive system, and cause hepatotoxicity and nephrotoxicity (Hamdaoui et al, 2016;2018;.…”
Section: Introductionmentioning
confidence: 99%
“…The residue of G-based herbicides and its main metabolites, Aminomethylphosphonic acid (AMPA), are also found in foods, feed and ecosystems (Takahashi et al, 2001;Acquavella et al, 2004;Contardo-Jara et al, 2008). The consequences of the potential effects of these compounds on non-target organisms, such as humans or animals, have been highlighted (Williams et al, 2000;Tomlin 2006;Mangara et al, 2014). Besides, several studies have pointed out that these chemicals can adversely affect endocrine, reproductive, immune and renal systems (Gasnier et al, 2009;Clair et al, 2012;Mink et al, 2012).Recently, we showed that KL is an endocrine disruptor, which can interfere with the female reproductive system, and cause hepatotoxicity and nephrotoxicity (Hamdaoui et al, 2016;2018;.…”
Section: Introductionmentioning
confidence: 99%
“…According to Adigun (2001) and Kasongo (2009) in tropical areas management of weed remains manual because agriculture is mainly peasant. Besides this management mode, herbicides products reduce the frequency of interventions by weeding time savings estimated between 40-60% (Mangara et al, 2014).…”
Section: Am J Plantmentioning
confidence: 99%
“…According to Adigun (2001) and Kasongo (2009) in tropical areas management of weed remains manual because agriculture is mainly peasant. Besides this management mode, herbicides products reduce the frequency of interventions by weeding time savings estimated between 40-60% (Mangara et al, 2014).This study has set itself the objective of improving common bean crop production by using different weed management modes and highlighting their impact on the weed flora. …”
mentioning
confidence: 99%
“…Dans cette optique, tous les moyens possibles pour obtenir un rendement plus haut ont été engagés. Cependant, du fait de la pénibilité des opérations, de la rareté de la main d'oeuvre pour l'opération de désherbage et autres, les herbicides sont devenus le nouvel outil de travail des producteurs (Mangara et al, 2014). Par ailleurs, les producteurs recourent davantage aux intrants de synthèse tels que les engrais minéraux NPK (18-46-0) et urée (46 % N) malgré la faible la fertilité des bas-fonds (Yabi et al, 2017).…”
Section: Introductionunclassified